2021
DOI: 10.1155/2021/6103092
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Critical Factors of Postoperative Arrhythmia and Preventive Measures of Deep Venous Thrombosis

Abstract: The study focused on the risk factors of postoperative arrhythmia and lung infection and the preventive effects of targeted low-molecular-weight heparin (LMWH) on the occurrence of deep venous thrombosis (DVT) in patients with esophageal/cardia cancer. In this article, 82 patients who were pathologically diagnosed with esophageal/cardia cancer and underwent surgical treatment were selected as the research subjects. According to the different preoperative treatment methods, the patients were divided into the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%